1. podane uklady rownan rozwiaz metoda podstawienia

a)
½x - y=4
2- ⅓(3y +6x)=0

b)
2x +3y=5(x-3)
4(x+5)-2(y-3)=34

c)
(2x+4) : 2 + (y+1):3=4
3(x+2)-2(y-2)=3x +12

d)
2y-4x=-2+y
2x+½=16

e)
1/6(9y+⅓x)=-1
8-y=-x

f)
½(2x-4y)=3
y+½x=0


2.Podane uklady rownan rozwiaz metoda przeciwnych wspolczynnikow
a)
4y=3x-4
2x=-3(y-5)-1

b)
x/5-y/4=4
3x+4y=-2

c)
(x-y):2+(x+y):3=4
2x-5y=4(x+3)+3(12-2y)


1

Odpowiedzi

2009-12-13T16:33:08+01:00
1,
a)
½x - y=4
2- ⅓(3y +6x)=0

-y=4-0,5x/*(-1)
2-y+2x=0

y=-4+0,5x
2-(-4+0,5x)=0

y=-4+0,5x
2+4-0,5x=0

y=-4+0,5x
-0,5x=-6/:(-0,5)

y=-4+0,5x
x=12

y=-4+0,5*12
x=12

y=-4+6
x=12

y=2
x=12

b)
2x +3y=5(x-3)
4(x+5)-2(y-3)=34

2x+3y=5x-15
4x+20-2y-6=34

2x-5x+3y=-15
4x-2y=34-20+6

-3x+3y=-15 /:3
4x-2y=20

-x+y=-5
4x-2y=20

y=-5+x
4x-2(-5+x)=20

y=-5+x
4x-10-2x=20

y=-5+x
2x=20+10

y=-5+x
2x=30/:2

y=-5+x
x=15

y=-5+15
x=15

y=10
x=15

c)
(2x+4) : 2 + (y+1):3=4 /*6
3(x+2)-2(y-2)=3x +12

3(2x+4)+2(y+1)=24
3x+6-2y-4=3x+12

6x+12+2y+2=24
3x+6-2y-4=3x+12

6x+2y=24-12-2
3x-3x-2y=12-6+4

6x+2y=10
-2y=10 /:(-2)

6x+2y=10
y=-5

6x+2*(-5)=10
y=-5

6x-10=10
y=-5

6x=10-10
y=-5

6x=0/:6
y=-5

x=0
y=-5


d)
2y-4x=-2+y
2x+½=16

2y-y-4x=-2
2x=16-0,5

y-4x=-2
2x=15,5 /:2

y-4x=-2
x=7,75

y-4*7,75=-2
x=7,75

y-31=-3
x=7,75

y=-3+31
x=7,75

y=28
x=7,7


f)
½(2x-4y)=3
y+½x=0

x-2y=3
y+½x=0

x=3+2y
y+0,5(3+2y)=0

x=3+2y
y+1,5+y=0

x=3+2y
y+y=-1,5

x=2+2y
2y=-1,5/:2

x=2+2y
y=-0,75

x=2+2*(-0,75)
y=-0,75

x=2-1,5
y=-0,75

x=0,5
y=-0,75

2,
a) 4y=3x-4
2x=-3(y-5)-1

-3x+4y=-4
2x=-3y-15-1

-3x+4y=-4
2x+3y=-16

-x+7y=-20
-x=-20-7y /*(-1)
x=20+7y

4y+3x= - 4
x=20+7y

4y+3(20+7y)=-4
x=20+7y

4y+30+21y=-4
x=20+7y

25y=-4-30
x=20+7y

25y=-34 /:25
x=20+7y

y=-1,36
x=20+7*(-1,36)

y=-1,36
x=20-9,52

y=-1,36
x=10,48